(untitled) (Raíces: Revista de Ciencias Sociales y Políticas, 2023)
The objective of this article is to analyze some of the dimensions of the subjectivation processes that young people who have been adopted go through in the metropolitan area of Buenos Aires in order to understand how they assume or distance themselves from the institutional categories used to catalog them, as well as of operations on their corporality and emotionality; they obey, evade or reappropriate institutional practices that seek to shape their conduct and produce effects on their subjectivities; They establish social relationships with their peers and from them they build knowledge about how to manage their future thanks to shared socio-biographical experiences. With these purposes, the article analyzes the stories constructed through in-depth, biographical interviews, carried out during the year 2019, with ten young people who were transferred to other family groups. The article argues that adoption as a “solution” for the search for those responsible for young people is being constituted throughout a process in which interactions with peers acquire a central place and in which reflection on their own is encouraged. actions and wills in order to become adoptable subjects.